Mekanisme Pengadaan Rumah Berbasis Syariah pada Perumahan Grand Cesar Residence Kabupaten Sintang - Puja Tsalitsa; Sumar’in; Tehedi (Equivalent : Journal of Economic, Accounting and Management, 2025)
Abstract : This research was conducted at the Grand Cesar Residence Housing. The community's need for houses with sharia principles continues to increase along with the number of newlyweds. The focus of this study is the Sharia-based housing procurement mechanism at the Grand Cesar Residence Housing, Sintang Regency and the Islamic economic review of the Sharia-based housing procurement mechanism at the Grand Cesar Residence Housing, Sintang Regency. This study uses a qualitative descriptive approach and the type of research uses a case study. This research was conducted at the Grand Cesar Residence Housing, Sintang Regency, located at Jalan Mensiku Jaya, Kapuas Kiri Hulu Village, Sintang District. The primary data sources used include the Owner and Housing Developer and consumers. Data collection techniques are interviews, observation and documentation. Data analysis techniques are data collection, data reduction, data presentation and drawing conclusions/verification. Data validity checking techniques include credibility, transferability, dependability and confirmability. The results of the study show that (1) The mechanism for procuring sharia-based houses at the Grand Cesar Residence Housing Complex in Sintang Regency applies the principle of ta'awun (mutual assistance) with the al-qard (loan) contract, namely that each consumer helps each other with their respective installments for building a house. (2) The Islamic economic review of the mechanism for procuring sharia-based houses at the Grand Cesar Residence Housing Complex in Sintang Regency is by carrying out no usury, no fines, no seizure and tadlis. However, there is still gharar, and gharar in this case is small gharar, meaning that according to the majority of scholars, small gharar is permitted because of something that cannot be avoided, such as the delay in the time of building a house because there are consumers who are not on time in paying installments. Abstrak : Penelitian ini dilakukan pada Perumahan Grand Cesar Residence. Kebutuhan masyarakat akan rumah dengan prinsip-prinsip syariah terus meningkat seiring banyaknya pasangan pernikahan baru.  Fokus dalam penelitian ini adalah Mekanisme pengadaan rumah berbasis syariah pada Perumahan Grand Cesar Residence Kabupaten Sintang dan Tinjauan ekonomi Islam terhadap mekanisme pengadaan rumah berbasis syariah pada Perumahan Grand Cesar Residence Kabupaten Sintang. Penelitian ini menggunakan pendekatan kualitatif deskiptif dan jenis penelitian menggunakan  studi kasus. Penelitian ini dilaksanakan di Perumahan Grand Cesar Residence Kabupaten Sintang yang beralamat di Jalan Mensiku Jaya, Kelurahan Kapuas Kiri Hulu, Kecamatan Sintang. Sumber data primer yang digunakan diantaranya Owrner sekaligus Developer perumahan dan konsumen. Teknik pengumpulan data yaitu wawancara, observasi dan dokumentasi. Teknik analisis data yaitu pengumpulan data, reduksi data, penyajian data dan menarik kesimpulan/verifikasi. Teknik pengecekan keabsahan data meliputi credibility, transferability, dependability dan confirmability. Hasil penelitian menunjukkan, (1) Mekanisme pengadaan rumah berbasis syariah pada Perumahan Grand Cesar Residence Kabupaten Sintang menerapkan asas ta’awun (tolong-menolong) dengan akad al-qard (pinjaman) yakni setiap konsumen saling membantu dengan angsurannya masing-masing untuk pembangunan rumah. (2) Tinjauan ekonomi Islam terhadap mekanisme pengadaan rumah berbasis syariah pada Perumahan Grand Cesar Residence Kabupaten Sintang yaitu dengan mengusung tanpa riba, tanpa denda, tanpa sita dan tadlis. Namun masih terdapat gharar, adapun gharar dalam hal ini yaitu gharar yang kecil, artinya menurut jumhur ulama gharar kecil dibolehkan karena sesuatu yang tidak bisa dihindari seperti mundurnya waktu pengerjaan rumah karena terdapat konsumen yang tidak tepat waktu dalam membayar angsuran.